2018
DOI: 10.1177/1541931218621278
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficacy of Using Hand Tremors for Early Detection of Hypoglycemic Events: A Scoping Literature Review

Abstract: Diabetes is a prevalent condition affecting millions of patients globally. Some diabetic patients suffer from a deadly condition called Hypoglycemia (sudden drop in blood glucose levels). Continuous Glucose Monitors (CGMs) have been the most pervasive tool used to track blood glucose levels but these tools are invasive and costly. While early detection of hypoglycemia has been studied, current approaches do not leverage tremors; which are a primary symptom of hypoglycemia. A scoping review was conducted to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…A nationwide survey of 212 patients with type 1 diabetes was conducted to investigate noticeability of hypoglycemic tremors as well as perceived frequency and severity of such tremors among patients. Our findings suggest that while tremors are perceived to be less noticeable, frequent, or severe than other hypoglycemic symptoms such as sweating, changes in body temperature, and headache, in line with the literature [19,21], such hypoglycemic tremors occur at moderate frequency and are being noticed by most patients. Indeed, our study shows that more than 50% of the respondents encountered hypoglycemic events at least once a week.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A nationwide survey of 212 patients with type 1 diabetes was conducted to investigate noticeability of hypoglycemic tremors as well as perceived frequency and severity of such tremors among patients. Our findings suggest that while tremors are perceived to be less noticeable, frequent, or severe than other hypoglycemic symptoms such as sweating, changes in body temperature, and headache, in line with the literature [19,21], such hypoglycemic tremors occur at moderate frequency and are being noticed by most patients. Indeed, our study shows that more than 50% of the respondents encountered hypoglycemic events at least once a week.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous review, we reported that tremors and trembling have been found to be very common among patients with diabetes [19]. In another study surveying elderly subjects, trembling was reported in 71% of patients with diabetes [21].…”
Section: Objectivesmentioning
confidence: 92%
See 2 more Smart Citations
“…With environmental factors greatly influencing the skin conductance and body temperature, these parameters are not accurate predictors of hypoglycemia [6]. Furthermore, our literature search revealed very few studies using hypoglycemic tremors or utilized technology to correlate tremors with the onset of hypoglycemia [7]. One study attempted to detect hypoglycemia through tremors as a continuous movement for more than 30 seconds in the wrist without specific analysis of the tremor characteristics.…”
Section: Introductionmentioning
confidence: 99%